Newly Emerging Standards of Auditor Responsibility. - Causey, Denzil Y. (The Accounting Review, 1976)
Abstract The article focuses on newly emerging standards of auditor responsibility. Although the basic problems confronting present day's auditor have been discussed for nearly 100 years, the newly emerging standards of care, materiality and independence would shock the auditor of past days. The purpose of this paper is to analyze these newly emerging standards of auditor responsibility. Responsibilities of public accountants, like those of other professionals, have increased greatly in complexity since 1931 when a judge held in the Ultramares Corp. case that public accountants are liable to third parties for fraud but not for ordinary negligence. The Ultramares case established stops number one, two and four on the variable scale of duties. The judge reasoned that public accountants also owe a duty to clients, creditors and investors to perform without fraud, which is stop number one on the scale. This has been interpreted to establish stop number two on the scale where auditors owe all third-party users a duty to base their opinions on honest belief and grounds for the belief.